Towards bond selective chemistry from first principles: Methane on metal surfaces - Shen, X. J. (2014)
Controlling bond-selective chemical reactivity is of great importance and has a broad range of applications. Here, we present a molecular dynamics study of bond selective reactivity of methane and its deuterated isotopologues (i.e., CH4−xDx, x=0,1,2,3,4) on Ni(111) and Pt(111) from first principles calculations. Our simulations allow for reproducing the full C-H bond selectivity recently achieved experimentally via mode-specific vibrational excitation and explain its origin. Moreover, we also predict the hitherto unexplored influence of the molecular translational energy on such a selectivity as well as the conditions under which the full selectivity can be realized for the a priori less active C-D bond.